In vivo identification of alteration of inner neurosensory layers in branch retinal artery occlusion. Issue 2 (22nd April 2011) - Ritter, Markus; Sacu, Stefan; Deák, Gábor G; Kircher, Karl; Sayegh, Ramzi G; Pruente, Christian; Schmidt-Erfurth, Ursula M
Abstract : Background/aims: To characterise the extension and progression of alteration of neurosensory layers following acute and chronic branch retinal artery occlusion (BRAO) in vivo using spectral-domain optical coherence tomography. Methods: In this observational case series, eight eyes with acute BRAO and nine eyes with chronic BRAO were analysed using a Spectralis Heidelberg Retina Angiograph (HRA)+optical coherence tomography system including eye tracking. Patients with acute BRAO were examined within 36±5 h after primary event and at weekly/monthly intervals thereafter. Segmentation measurements of all individual neurosensory layers were performed on single A-scans at six locations in affected and corresponding non-affected areas. The thickness values of the retinal nerve fibre layer together with the ganglion cell layer (NFL/GCL), inner plexiform layer (IPL), inner nuclear layer together with outer plexiform layer (INL/OPL), outer nuclear layer (ONL), and photoreceptor layers together with the retinal pigment epithelium (PR/RPE) were measured and analysed. Results: Segmentation evaluation revealed a distinct increase in thickness of inner neurosensory layers including the NFL/GCL (35%), IPL (80%), INL/OPL (48%) and mildly the ONL by 21% in acute ischaemia compared with corresponding layers in non-ischaemic areas. Regression of intraretinal oedema was followed by persistent retinal atrophy with loss of differentiation between IPL and INL/OPL at month 2. In contrast, the ONL and subjacent PR/RPE retained their physiological thickness in patients with chronic BRAO. Conclusion: In vivo assessment of retinal layer morphology allows a precise identification of the pathophysiology in retinal ischaemia.